Learning to Read and Write in the Multilingual Family - Wang, Xiao-lei (Parents' and Teachers' Guides, 2011)
This book is a guide for parents who wish to raise children with more than one language and literacy. Drawing on interdisciplinary research, as well as the experiences of parents of multilingual children, this book walks parents through the multilingual reading and writing process from infancy to adolescence. It identifies essential literacy skills at each developmental stage and proposes effective strategies that facilitate multiliteracy, in particular, heritage-language literacy development in the home environment. This book can also be used as a reference for teachers who teach in community heritage language schools and in school heritage (or foreign) language programmes